Linguistic Harmonization: Dissecting Alfiyah Ibn Malik with Chomsky's Transformational Generative Theory - Khoirul Mubin; Nasiruddin; Boby Bagas Purnama; Dionisia Folliero (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2024)
This study is motivated by the need to update and deepen the understanding of Alfiyah Ibnu Malik through a modern linguistic perspective, given the complexity of the 1,002 stanzas that are difficult for students with a weak language foundation to comprehend, and the existing gap in the literature regarding the application of Transformational Generative Theory (TGT) in Arabic grammar, which can help elucidate language structure and enhance understanding and interest in learning. This research aims to examine Alfiyah Ibnu Malik using the modern linguistic approach of Transformational Generative Theory (TGT). The research method applied is library research with a descriptive qualitative approach. The findings indicate that Transformational Generative Theory has specific characteristics in linguistic studies, including deep and surface structures, the concepts of competence and performance, as well as specific and general transformations. Additionally, TGT includes a universal grammar that can be applied to Alfiyah Ibnu Malik. The application of TGT to Alfiyah Ibnu Malik reveals that specific transformations occur in various aspects of Arabic grammar, including optional and obligatory deletion, optional substitution, optional replacement, optional expansion, optional addition, and optional and obligatory permutation.